2012
DOI: 10.3390/s130100001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Passive Sensor Array for Diagnosis of Loosening of Endoprosthetic Implants

Abstract: Currently, imaging methods are used to diagnose loosening of endoprosthetic implants, but fail to achieve 100% accuracy. In this study, a passive sensor array which is based on the interaction between magnetic oscillators inside the implant and an excitation coil outside the patient was investigated. The excited oscillators produce sound in the audible range, which varies according to the extent of loosening. By performing several experimental tests, the sensor array was optimized to guarantee reproducible and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Most THR stability assessment studies have focused on the femoral component [20][21][22][23][24][35][36][37][38][39][40][41][42]. Vibration analysis studies on acetabular loosening are limited because the acetabulum has a complex geometry compared to the femur and has a thicker overlaying soft tissue layer, which acts as a signal buffer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most THR stability assessment studies have focused on the femoral component [20][21][22][23][24][35][36][37][38][39][40][41][42]. Vibration analysis studies on acetabular loosening are limited because the acetabulum has a complex geometry compared to the femur and has a thicker overlaying soft tissue layer, which acts as a signal buffer.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous studies on vibration analysis [20][21][22][23][24][35][36][37][38][39][40][41][42] assessed loosening of the femoral stem. Since a high rate of loosening in the acetabular component has been reported in the clinically [43]; therefore, the aim of the present study was to compare ultrasound and accelerometer methods and to examine the viability of the vibration analysis technique to accurately detect acetabular component loosening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bringing monitoring to a patient rather than vice-versa provides a multitude of benefits. Without constant monitoring, particularly during stages of rehabilitation and recovery (Hii et al, 2011), patient relapse is shown to be far more common (Fong & Chung, 2013). Pressures on important medical resources in both equipment and medical professionals are reduced and significantly increased access to care means patients are given the freedom of being able to live much more independently, greatly improving their quality of life (Niewolny, 2013).…”
Section: Remote Patient Monitoringmentioning
confidence: 99%
“…14,15 For application in orthopedic and trauma surgery, a contact-free monitoring device is necessary. For this reason, a novel technology based on the principle of acoustic sound analysis was developed, allowing non-invasive acoustic excitation, [16][17][18] using a New Zealand White Rabbit (NZWR) model. The NZWR is a reasonable, cost-effective alternative to larger mammals.…”
mentioning
confidence: 99%